Information and communication technology : shaping our lives - Sylvester, Kenneth (GraceKennedy Foundation KingstonJM, 2007)
Deals with ICT in social and economic transformation and looks at the sector in Jamaica and the Caribbean. Examines efforts at using ICT to promote global competitiveness. Looks at the future beyond the Information Society.